Stroke-induced damage on the blood–brain barrier - Xue, Song; Zhou, Xin; Yang, Zhi-Hui; Si, Xiang-Kun; Sun, Xin (Frontiers in Neurology, 2023)
The blood–brain barrier (BBB) is a functional phenotype exhibited by the neurovascular unit (NVU). It is maintained and regulated by the interaction between cellular and non-cellular matrix components of the NVU. The BBB plays a vital role in maintaining the dynamic stability of the intracerebral microenvironment as a barrier layer at the critical interface between the blood and neural tissues. The large contact area (approximately 20 m2/1.3 kg brain) and short diffusion distance between neurons and capillaries allow endothelial cells to dominate the regulatory role. The NVU is a structural component of the BBB. Individual cells and components of the NVU work together to maintain BBB stability. One of the hallmarks of acute ischemic stroke is the disruption of the BBB, including impaired function of the tight junction and other molecules, as well as increased BBB permeability, leading to brain edema and a range of clinical symptoms. This review summarizes the cellular composition of the BBB and describes the protein composition of the barrier functional junction complex and the mechanisms regulating acute ischemic stroke-induced BBB disruption.